Sport events and happiness: towards the development of a measuring instrument*. Issue 4 (1st October 2016) - Littlejohn, Meagan; Taks, Marijke; Wood, Laura; Snelgrove, Ryan
ABSTRACT: The purpose of this study was to create a measuring instrument to capture happiness in the context of events and test it in the context of two non-mega-sport events. Three groups of residents were distinguished (event 1: Ontario Summer Games (OSG); event 2: Ontario 55 + Summer Games (55 + SG); and a control group, unaware of events: CONTR). Residents who did not attend the events were surveyed in public places in order to find out whether the mere hosting of these events had the potential to impact their happiness and well-being. The theoretical construct of subjective well-being was used to develop a survey to measure happiness and well-being holistically. Four components were developed: overall level of happiness (one item), satisfaction with important domains (three items), and specific emotions recently experienced (i.e. affect dimensions, eight items). Exploratory factor analyses confirmed one construct for satisfaction; and two constructs for the affect dimensions: positive affect (three items) and reversed negative affect (five items). ANOVAs revealed that residents aware of the 55 + SG, an "older age" sport event, reported significantly higher levels of overall happiness and satisfaction than the control group. Moreover, the 55 + SG showed significantly lower levels of negative emotions than the OSG and control groups. The results do not strongly support the notion that different types of events affect residential happiness in different ways. Future research should explore the impacts of other types of sport events on residential happiness and well-being, and account for socio-demographic factors, involvement with the event, and the weather to more precisely discern the impacts of events on residential happiness.